Semi‐idealized simulations of wintertime flows and pollutant transport in an Alpine valley: Origins of local circulations (Part I). (28th January 2020) - Sabatier, Tiphaine; Paci, Alexandre; Lac, Christine; Canut, Guylaine; Largeron, Yann; Masson, Valéry
Abstract: Mountainous terrains are known for driving their own dynamics which respond to the local morphological arrangement of the area. Thermally driven flows in particular develop at slope and valley scales and ensure a certain degree of pollutant dispersion under quiescent wintertime synoptic conditions. The present study focuses on a section of the Arve River valley situated close to Mont Blanc which frequently suffers from severe pollution episodes under stable wintertime conditions whilst surrounding valleys appear to be less affected. The particular shape of this basin‐like section and its location at the confluence of several tributary valleys raises the question of the extent to which local circulations participate in pollutant trapping over restricted sectors. A set of high‐resolution numerical simulations are designed in order to improve our understanding of the local flow structure and their sensitivity to thermal stratification, radiative forcing and snow cover. The tributary valleys play a major role in both daytime and night‐time dynamics by deflecting the entering daytime flux and constraining the night‐time flow trajectories. In addition, the basin morphology greatly influences the circulations. During daytime a two‐layer wind structure is developed and driven by spatial variations in sun exposure which is particularly heterogeneous under wintertime forcing. Early spring radiative forcing or the presence of snow allow both of them to develop more homogeneous circulations through the reduction of sun exposure variations, except when snow cover is restricted to shaded basin sidewalls. At night, a three‐layer wind structure is developed. It favours air mass ventilation in the western linear branch of the basin whilst stagnation and recirculation prevail in the curved part of the valley which is also the most polluted. This study therefore highlights spatial variations in circulation patterns consistent with the accumulation of observed pollutants and their heterogeneous distribution. Abstract : Local thermally driven circulations play a major role in Alpine valleys by representing one of the only sources for pollutant dispersion under stratified wintertime conditions. The study focuses on the slope‐ and valley‐scale flows developed within a complex Alpine basin associated with poor air quality. The origins of the flows along with their sensitivity to several processes are characterized from a set of high‐resolution numerical simulations run in a semi‐idealized framework which is based on the Passy‐2015 field experiment.